Fiscal Management in Federal Democracies : Argentina and Brazil - Webb, B. Steven (The World Bank, 1999)
May 1999 - Argentina and Brazil-two of the most decentralized public sectors in Latin America and (along with Colombia and India) among the most decentralized democracies in the developing world-faced similar problems in the 1980s: excessive public deficits and high inflation exacerbated by subnational deficits. In the 1990s, Argentina was more successful at macroeconomic stabilization, partly because it imposed harder budget constraints on the public sector nationally and partly because it had stronger party control of both national legislators and subnational governments. In shifting to decentralized public finances, a country's central government faces certain fiscal management problems. First, during and soon after the transition, unless it reduces spending or increases its own tax resources, the central government tends to have higher deficits as it shifts fiscal resources to subnational governments through transfers, revenue sharing, or delegation of tax bases. Reducing spending is hard not only because cuts are always hard but because subnational governments might not take on expected tasks, leaving the central government with a legal or political obligation to continue spending for certain services. Second, after decentralization, the local or state government faces popular pressure to spend more and tax less, creating the tendency to run deficits. This tendency can be a problem if subnational governments and their creditors expect or rely on bailouts by the central government. Econometric evidence from 32 large industrial and developing countries indicates that higher subnational spending and deficits lead to greater national deficits. Dillinger and Webb investigate how, and how successfully, Argentina and Brazil dealt with these problems in the 1990s.